Knowledge-based bioeconomy: The use of intellectual capital in food industry of Serbia - Jelena Djordjevic Boljanovic; Gordana Dobrijevic; Slobodan Cerovic; Slavko Alcakovic; Filip Djokovic (Amfiteatru Economic Journal, 2018)
The main objective of this exploratory study was to identify and analyse the indicators of intellectual capital in food industry of Serbia. The study investigated managers' perceptions of their usefulness, practical application, and factors that influence them. The respondents were surveyed by means of a questionnaire. They were mainly top managers from 18 food organizations, committed to the bioeconomy paradigm. The survey items were divided into three subcategories, namely human, structural, and relational capital. The data were analysed by the SPSS 21 statistical software. The results show that all indicators were perceived as very important, relational capital indicators being the most useful of all. Of all individual items, employee motivation, market share, and employee satisfaction were perceived as the most important. This study provides a perspective on managing intellectual capital in bioeconomy.
Keywords: Q57; O34; 330; knowledge-based bioeconomy; intellectual capital; human capital; structural capital; relational capital; intellectual capital indicators; Serbia's food industry